Waqf Law is Relevant in Responding to the Challenges of the Age Regarding the Law of Selling Waqf Goods: Study of the Book of Fathul Mu'in by Syaih Zainuddin Bin Abdul Aziz Al-Malibari - Waluyo Waluyo (Gema Wiralodra, 2023)
This study aims to provide a deeper understanding and offer solutions to the statements in the book. The research method used is qualitative research with a normative legal approach or library research. Contextual analysis was carried out to understand and analyze in depth the contents of the book "Fathul Mu'in". The results of the review show that the sale of waqf goods in the book is not permissible, even though the goods are damaged. This finding emphasizes the importance of understanding the views of texts in various literature and including the arguments and opinions of other scholars to provide solutions to problems that often arise in today's society. Syekh Ahmad Zainuddin Al-Malibari is based on the law of the Ash-Shafi'i school of thought and prioritizes opinions that are in line with him in waqf law. However, the suggestion of fiqh states that every case must be adjusted to its purpose. This approach is in line with the hadith which states that every action depends on the intention. Some scholars also argue that the important thing is to preserve the old, which is good and take the new, which is better. Problem solving in religion basically aims for the benefit of religion and people in general. Some scholars also argue that the important thing is to preserve the old, which is good and take the new, which is better. Problem solving in religion basically aims for the benefit of religion and people in general. Some scholars also argue that the important thing is to preserve the old, which is good and take the new, which is better. Problem solving in religion basically aims for the benefit of religion and people in general.